The impact of school closures on pandemic influenza:Assessing potential repercussions using a seasonal SIR model - Sherry Towers; Katia Vogt Geisse; Chia-Chun Tsai; Qing Han; Zhilan Feng (Mathematical Biosciences and Engineering)
When a new pandemic influenza strain has been identified, mass-production of vaccines can take several months, andantiviral drugs are expensive and usually in short supply.Social distancing measures, such as school closures, thus seem an attractive means to mitigate disease spread.However, the transmission of influenza is seasonal in nature, and as has been noted in previousstudies,a decrease in the average transmission rate in a seasonal disease modelmay result in a larger final size.In the studies presented here,we analyze a hypothetical pandemic using a SIR epidemic model with time- and age-dependent transmissionrates; using this model weassess and quantify, for the first time, thethe effect of the timing and length of widespread school closures oninfluenza pandemic final size and average peak time.  &nbsp We find that the effect on pandemic progression strongly depends on the timing of the start of the school closure.For instance, we determine that schoolclosures during a late spring wave of an epidemiccan cause a pandemic to become up to 20% larger, but have the advantage that theaverage time of the peak is shifted by up to two months, possibly allowing enough time for development ofvaccines to mitigate the larger size of the epidemic.Our studies thus suggest that when heterogeneity intransmission is a significant factor, decisions of public health policy will be particularlyimportant as to how control measures such as school closures should be implemented.